2015
DOI: 10.1039/c4cp05659k
|View full text |Cite
|
Sign up to set email alerts
|

Planar pentacoordinate carbons in CBe54− derivatives

Abstract: The potential energy surfaces of a series of clusters with formula CBe5Lin(n-4) (n = 1 to 5) have been systematically explored. Our computations show that the lithium cations preserve the CBe5(4-) pentagon, such that the global minimum structure for these series of clusters has a planar pentacoordinate carbon (ppC) atom. The systems are primarily connected via a network of multicenter σ-bonds, in which the C atom acts as σ-acceptor and this acceptance of charge is balanced by the donation of the 2pz electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 48 publications
(7 reference statements)
1
47
0
Order By: Relevance
“…If a lithium cation interacts with the CE 4 2− fragment, it can be linked to a couple of E atoms (Figure ) to form a planar structure (E=Al and Ga), or directly to the carbon atom to yield a pentacoordinate carbon with a square‐pyramidal geometry (E=In, Tl). Notably, all of the previous clusters, both CE 4 2− and CE 4 Li − , have 18‐valence electrons . This building rule has been exploited to propose, on paper, several planar hypercoordinate carbon atoms, such as CAl 5 + , which is the first cluster in which the global minimum structure possesses a planar pentacoordinate carbon atom .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a lithium cation interacts with the CE 4 2− fragment, it can be linked to a couple of E atoms (Figure ) to form a planar structure (E=Al and Ga), or directly to the carbon atom to yield a pentacoordinate carbon with a square‐pyramidal geometry (E=In, Tl). Notably, all of the previous clusters, both CE 4 2− and CE 4 Li − , have 18‐valence electrons . This building rule has been exploited to propose, on paper, several planar hypercoordinate carbon atoms, such as CAl 5 + , which is the first cluster in which the global minimum structure possesses a planar pentacoordinate carbon atom .…”
Section: Introductionmentioning
confidence: 99%
“…Notably,a ll of the previous clusters, both CE 4 2À andC E 4 Li À ,h ave 18-valence electrons. [24][25][26][27][28][29] This building rule has been exploited to propose, on paper, severalp lanar hypercoordinate carbon atoms, such as CAl 5 + , [30] which is the first cluster in which the global minimum structure possesses ap lanarp entacoordinate carbon atom. [10] In contrast, the carbon atom in CAl 5 ,w ith 19-valence electrons,a dopts at etrahedral environment.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Doped hydrocarbons or carbon clusters with lithium, 23 beryllium/boron, 24,25 boron, [26][27][28][29][30] nitrogen, 31 silicon, 32 phosphorus, 33,34 and late transition metals 35 with a ptC, ptB, ptN, ptSi, or ptP atom are also reported. It is worth to note here that planar penta, [36][37][38][39][40][41][42][43] hexa, [44][45][46][47][48] and hepta 49,50 coordinated carbon compounds are also actively pursued due to the potential implications of these molecules in making new materials. 51 In this work, we explored the dissociation pathways of three different isomers of C 7 H 2 , which contain a ptC atom.…”
Section: Introductionmentioning
confidence: 99%
“…However, further on, it was shown that neither C 6 Li 6 nor Si 6 Li 6 has a star‐like minimum structure . Nevertheless, it inspired our research group to successfully explore other clusters, such as Si 5 Li 7 + , C 5 Al 5 − , C 5 Li 7 + , and CBe 5 Li 5 + , whose lowest energy structures do adopt a star‐like form (Figure c–f).…”
Section: Introductionmentioning
confidence: 99%